2018
DOI: 10.1155/2018/6452721
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Tuberculosis Diagnosed during Operative Laparoscopy for Suspected Ovarian Cancer

Abstract: Background While the combination of a pelvic mass, very high serum level of CA-125, chest adenopathy, and ascites is concerning for advanced-stage ovarian cancer, the etiology of such a presentation can be due to disseminated pelvic tuberculosis. Case A 67-year-old para 2 African-American woman presented with abdominal pain and shortness of breath. Subsequent CT and MR imaging demonstrated chest adenopathy, a pelvic mass, omental caking, and ascites. The patient underwent diagnostic laparoscopy with biopsy rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Laparoscopy can detect more cases of genital TB and abdominal TB by direct viewing of the abdomen and pelvis for various TB findings. Definite findings like beaded tubes, caseous nodules or tubercles or probable findings such as encysted ascites, pelvic, abdominal or perihepatic adhesions, hydrosalpinx, pyosalpinx or tubo-ovarian masses and tubal blockage are seen 5 , 6 , 9 , 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopy can detect more cases of genital TB and abdominal TB by direct viewing of the abdomen and pelvis for various TB findings. Definite findings like beaded tubes, caseous nodules or tubercles or probable findings such as encysted ascites, pelvic, abdominal or perihepatic adhesions, hydrosalpinx, pyosalpinx or tubo-ovarian masses and tubal blockage are seen 5 , 6 , 9 , 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy by direct visualization of the abdomen and pelvis can detect most cases of FGTB missed by traditional tests and can be a part of CRS thus, can show a definite or probable finding of FGTB and also help in prognostication of infertility in addition to plan further treatment 5 , 9 , 12 - 14 . Although previous smaller studies of short duration have observed laparoscopy to be useful in the detection of FGTB, a bigger study with large sample size is needed for confirmation of findings of the prior studies.…”
mentioning
confidence: 99%
“…Clinically, female genital tract TB usually impacts menstruation, causing amenorrhea, oligomenorrhea, and infertility. Tuberculosis may erode the endometrium and severe body consumption may explain its mechanism [14]. The most common intraoperative findings in TBP are tubo-ovarian masses, ascites, pelvic adhesions, perihepatic adhesions, and caseous or granulomatous nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes the diagnosis of TBP can be made instantly when small tubercles (milia) are noted on the peritoneum, but when milia are not present, frozen section is also useful intraoperatively and can avoid unwarranted, extensive surgery [15]. Laparoscopic biopsies of the suspected lesions are an adequate and safe method to make available tissue samples for histologic and bacteriologic diagnosis of TB infection with sensitivity > 80%, especially in the presence of ascites [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy has the advantage of direct visualisation of the abdomen and pelvis for subtle signs of FGTB and can show a definite or probable finding of FGTB and can also help in prognostication of infertility and to plan further treatment. [ 1 2 3 9 10 11 ] However, laparoscopy may be hazardous in FGTB and abdominopelvic TB. [ 12 ] The purpose of the current study was to observe difficulties and complications observed in FGTB patients as compared to control cases of laparoscopy performed for infertility in the absence of FGTB.…”
Section: Introductionmentioning
confidence: 99%